"Whatdunit?" Developmental changes in children's syntactically based sentence interpretation abilities and sensitivity to word order. (25th November 2015) - MONTGOMERY, JAMES W.; EVANS, JULIA L.; GILLAM, RONALD B.; SERGEEV, ALEXANDER V.; FINNEY, MIANISHA C.
ABSTRACT: Aim 1 of this study was to examine the developmental changes in typically developing English-speaking children's syntactically based sentence interpretation abilities and sensitivity to word order. Aim 2 was to determine the psychometric standing of the novel sentence interpretation task developed for this study, because we wish to use it later with children with specific language impairment. Children listened to semantically implausible sentences in which noun animacy and the natural affordance between the nouns were removed, thus controlling for event probability. Using this novel "whatdunit?" agent selection task, 256 children 7–11 years old listened to two structures with canonical word order and two with noncanonical word order. After each sentence, children selected as quickly as possible the picture of the noun they believed was "doing the action." Children interpreted sentences with canonical word order with greater accuracy and speed than those with noncanonical word order. Older children (mean age = 10 years, 8 months) were more accurate and faster than younger children (mean age = 8 years, 1 month) across all sentence forms. Both older and younger children demonstrated similar error patterns across sentence type. The "whatdunit?" task also proved to have strong validity and reliability, making it suitable for studies with children with specific language impairment.